Hemoglobin to red cell distribution width ratio as a prognostic marker for ischemic stroke after mechanical thrombectomy - Feng, Xianrong; Zhang, Yaodan; Li, Qizheng; Wang, Baojia; Shen, Jie (Frontiers in Aging Neuroscience, 2023)
Background The hemoglobin to red cell distribution width ratio (HRR) has been experimentally associated with the prognosis of acute ischemic stroke (AIS). However, its relationship with mechanical thrombectomy (MT) for AIS remains unclear. Therefore, this study aimed to investigate the relationship between HRR at admission, follow-up HRR, and clinical outcomes in patients undergoing MT. Methods Acute ischemic stroke patients undergoing MT were consecutively enrolled from January 2017 to December 2022. Demographic, clinical, and laboratory information were collected. HRR was measured by dividing hemoglobin (Hb) by red cell distribution width (RDW) at admission and after 24 h of MT. Clinical outcomes after 3 months were evaluated using the modified Rankin Scale (mRS). The primary outcome was poor prognosis (mRS > 2) at 3 months, while the secondary outcome was death within 3 months. Results A total of 310 patients were analyzed, of whom 216 patients (69.7%) had poor prognosis, and 92 patients (29.6%) died. Patients with a poor prognosis and death had significantly lower HRR levels at admission and after 24 h. HRR at admission was not associated with clinical outcomes according to multivariable logistic regression analysis. However, HRR after 24 h was significantly associated with poor prognosis (adjusted odds ratio [OR]: 0.646, 95% confidence interval [CI]: 0.520–0.803, p < 0.001) and death (adjusted OR: 0.615, 95% CI: 0.508–0.744, p < 0.001). Receiver-operating characteristic curve analysis demonstrated the predictive ability of HRR after 24 h, with areas under the curves of 0.790 for poor prognosis and 0.771 for death. Conclusion Rapidly measurable HRR levels are an independent marker of outcome after MT in AIS patients. This may provide a reliable auxiliary outcome measure for clinical routine and interventional therapy.